Antibacterial Potential of West Kalimantan Local Bajakah (Spatholobus suberectus) Ethanol Extract against Micrococcus luteus - Laili Fitri Yeni; Nury Kamelia; Chaerani (Quagga: Jurnal Pendidikan dan Biologi, 2023)
Bajakah Jie Xue Teng (Spatholobus suberectus) is an endemic plant from West Kalimantan which is the potential as a natural antimicrobial, but its antimicrobial ability has not been widely reported so that it can be tested on Micrococcus luteus bacteria which is the agent causing dandruff. The purpose of this study is to describe the phytochemical content of Jie Xue Teng (Spatholobus suberectus) bajakah ethanol extract and its potential to inhibit M. luteus in vitro. The phytochemical content of the extract was tested using the Thin Layer Chromatography (TLC) method. The type of research is a laboratory experiment using the Kirby Baeur disk diffusion method with swab technique with a series of extract concentrations of 1000 mg/ml, 500 mg/ml, 250 mg/ml, and 125 mg/ml, positive control (30% amoxilin), and negative control (DMSO 10%) with 4 repetitions. The phytochemical content of the ethanol extract of bajakah that was tested shows secondary metabolites of steroids, flavonoids, saponins, and alkaloids. Bajakah ethanol extract has the inhibitory potential against M. luteus for all test concentrations which fall under the moderate category. The diameter of the amoxicillin inhibition zone was still larger than the extract inhibition zone.